Exploitation of Women in Virtual Spaces: A New Challenge to Islamic Law in the Post-Truth Era - Rafki, Muhammad; Dasopang, Nur Sania (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
The exploitation of women in social media has become a worrying phenomenon in the digital era, where women are often used as objects to attract public attention, increase popularity, or maximize commercial profits. This phenomenon includes various forms of objectification, stereotyping, and the spread of content that degrades women's dignity. This research aims to examine this phenomenon from a critical perspective of Islamic law, by focusing on the protection of human honor (hifz al-'ird) as one of the main elements in maqashid al-shari'ah. The research method used is a normative approach with descriptive-qualitative analysis of relevant Islamic legal principles, including the prohibition of actions that degrade individual dignity, the need to maintain women's honor, and moral responsibility in the media. The study also analyzes factors that encourage women's exploitation on social media, such as content commercialization, patriarchal culture, and the lack of effective regulation on digital platforms. The results of the study show that the exploitation of women in social media is contrary to the values of justice and respect for human dignity in Islam. Furthermore, Islamic law mandates the need for strict supervision and regulation to prevent exploitative acts, and emphasizes the importance of media ethics education for the community. This study makes an important contribution in formulating a strategy based on Islamic law to overcome the exploitation of women on social media, as well as encouraging the creation of a fairer and more dignified digital ecosystem.